Contribution of the Retrovirus Epidemiology Donor Study (REDS) to research on blood transfusion safety in Brazil - Paula Loureiro; Cesar de Almeida-Neto; Anna Bárbara Carneiro Proietti; Ligia Capuani; Thelma Terezinha Gonçalez; Claudia Di Lorenzo de Oliveira; Silvana Carneiro Leão; Maria Inês Lopes; Divaldo Sampaio; Giuseppina Maria Patavino; João Eduardo Ferreira; Paula Fraiman Blatyta; et al. (Revista Brasileira de Hematologia e Hemoterapia, 2014)
The Retrovirus Epidemiology Donor Study (REDS) program was established in the United States in 1989 with the purpose of increasing blood transfusion safety in the context of the HIV/AIDS and human T-lymphotropic virus epidemics. REDS and its successor, REDS-II were at first conducted in the US, then expanded in 2006 to include international partnerships with Brazil and China. In 2011, a third wave of REDS renamed the Recipient Epidemiology and Donor Evaluation Study-III (REDS-III) was launched. This seven-year research program focuses on both blood banking and transfusion medicine research in the United States of America, Brazil, China, and South Africa. The main goal of the international programs is to reduce and prevent the transmission of HIV/AIDS and other known and emerging infectious agents through transfusion, and to address research questions aimed at understanding global issues related to the availability of safe blood. This article describes the contribution of REDS-II to transfusion safety in Brazil. Articles published from 2010 to 2013 are summarized, including database analyses to characterize blood donors, deferral rates, and prevalence, incidence and residual risk of the main blood-borne infections. Specific studies were developed to understand donor motivation, the impact of the deferral questions, risk factors and molecular surveillance among HIV-positive donors, and the natural history of Chagas disease. The purpose of this review is to disseminate the acquired knowledge and briefly summarize the findings of the REDS-II studies conducted in Brazil as well as to introduce the scope of the REDS-III program that is now in progress and will continue through 2018.